Duality of the Ego and the Inevitable Fate in the Novel "Kamrad" by Al-Ziwani: A Deconstructive Approach to the Introduction - Megharbi, Mouhamed Reda (Milev Journal of Research and Studies, 2023)
Illegal immigration is a humanitarian phenomenon that presents a challenge to European Union governments; Especially those facing the African coasts, from which boats carrying dozens of people depart almost every day. They are illegal immigrants, of various races, religions, and languages, but their goal is one to win anchoring on the northern bank, where the lost paradise awaits them. ! This novel, which we have in our hands, "Kamrad" (Al-Ziwani, 1st 2016) and the introduction in particular - as the text on which we are working in this approach - attempts to shed light on an impressive scene depicting the sinking of a Negro African boat, and a moment of recollection without which one of the drowned wrote on a paper and placed it inside a bottle that was thrown out by waves. The sea on the Italian coast. It is the duality of the ego and the inevitable fate, as we expressed in the title of the study, to indicate the dreams of the African ego that was suspended on the boat of life, but with the inevitability of the cosmic fate it was a boat of death and an inevitable fate for the cosmic laws of God, from which only the abnormal and the abnormal cannot be measured.Moments conveyed by the novel in its introduction tried to deal with it from the standpoint of the deconstructive approach, in order to disassemble and then rearrange the scene based on the duality of external and internal intertextuality.